DESCRIPTIVE STATISTICAL ANALYSIS OF UTAUT 2 FACTORS IN THE ADOPTION OF LIVIN’ MERCHANT BY BUSINESS ACTORS IN GREATER SURABAYA (Proceeding of SINERGY, 2026)
The rapid development of digital technology has driven the adoption of technology-based payment and banking services, including merchant banking services, as part of Indonesia’s digital financial transformation. One of the services designed for business actors is Livin’ Merchant, which is expected to support operational efficiency and transaction digitalization for micro, small, and medium enterprises (MSMEs). However, in its implementation, the adoption of Livin’ Merchant still faces several challenges, such as technical issues, limited facility support, as well as users’ perceived risk and trust levels. This study aims to descriptively analyze the factors influencing the adoption of Livin’ Merchant by business actors in Greater Surabaya using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model, extended with perceived security, perceived risk, institutional trust, and technology trust variables. This research employs a descriptive quantitative approach, with data collected through a seven-point Likert-scale questionnaire distributed to 403 business actors in Greater Surabaya. The data were analyzed using descriptive statistics, including mean, median, standard deviation, minimum, and maximum values. The results show that performance expectancy has the highest mean value of 6.17, indicating that business actors believe Livin’ Merchant can improve business performance and efficiency. In addition, habit (5.91), institutional trust (5.89), perceived security (5.84), and technology trust (5.76) also show high mean values, reflecting habitual use and strong trust in the Livin’ Merchant service and technology. In contrast, facilitating conditions (4.27) and perceived risk (4.02) have relatively lower mean values, indicating limitations in facility and technical support as well as concerns regarding usage risks. These findings suggest that improving system stability, strengthening facility and technical support, and enhancing security and risk management should be key priorities for banks to increase business actors’ trust and promote the sustainable adoption of Livin’ Merchant.